America in the world a history in documents from the War with Spain to the War on Terror - Engel, Jeffrey A. 1972-; Lawrence, Mark Atwood 1965-; Preston, Andrew 1973- (America in the world series, 2023)
"A wide-ranging anthology of primary texts in American foreign relations—now expanded to include documents from the Trump years to today How should America wield its power beyond its borders? Should it follow grand principles or act on narrow self-interest? Should it work in concert with other nations or avoid entangling alliances? America in the World captures the voices and viewpoints of some of the most provocative, eloquent, and influential people who participated in these and other momentous debates. Now fully revised and updated, this anthology brings together primary texts spanning a century and a half of U.S. foreign relations, illuminating how Americans have been arguing about the nation’s role in the world since its emergence as a world power in the late nineteenth century. Features more than 250 primary-source documents, reflecting an extraordinary range of views Includes two new chapters on the Trump years and the return of great power rivalries under Biden Sweeps broadly from the Gilded Age to emerging global challenges such as COVID-19 Shares the perspectives of presidents, secretaries of state, and generals as well as those of poets, songwriters, clergy, newspaper columnists, and novelists Also includes non-American perspectives on U.S. power"